Exchange rate smoothing in Hungary - Péter Karádi (Magyar Nemzeti Bank, 2005)
The paper proposes a structural empirical model capable of examining exchange rate smoothing in the small, open economy of Hungary. The framework assumes the existence of an unobserved and changing implicit exchange rate target. The central bank is assumed to use interest rate policy to obtain this preferred rate in the medium term, while market participants are assumed to form rational expectations about this target and influence exchange rates accordingly. The paper applies unobserved variable method - Kalman filtering - to estimate this implicit exchange rate target, and simultaneously estimate an interest rate rule and an exchange rate equation consistent with this target. The results provide evidence for exchange rate smoothing in Hungary by providing an estimated smooth implicit exchange rate target development and by showing significant interest rate response to the deviation of the exchange rate from this target. The method also provides estimates for the ceteris paribus exchange rate effects of expected and unexpected interest rate changes.
Keywords: E52; F31; F41; 330; exchange rate smoothing; interest rate rules; Kalman filter; Wechselkurspolitik; Zinspolitik; Ungarn; Zustandsraummodell